The Model of PPARγ-Downregulated Signaling in Psoriasis - Vladimir Sobolev; Anastasia Nesterova; Anna Soboleva; Evgenia Dvoriankova; Anastas Piruzyan; Dzerassa Mildzikhova; Irina Korsunskaya; Oxana Svitich (PPAR Research)
Interactions of genes in intersecting signaling pathways, as well as environmental influences, are required for the development of psoriasis. Peroxisome proliferator-activated receptor gamma (PPARγ) is a nuclear receptor and transcription factor which inhibits the expression of many proinflammatory genes. We tested the hypothesis that low levels of PPARγ expression promote the development of psoriatic lesions. We combined experimental results and network functional analysis to reconstruct the model of PPARγ-downregulated signaling in psoriasis. We hypothesize that the expression of IL17, STAT3, FOXP3, and RORC and FOSL1 genes in psoriatic skin is correlated with the level of PPARγ expression, and they belong to the same signaling pathway that regulates the development of psoriasis lesion.